Estrogen monotherapy in women with surgical menopause - T V Ovsyannikova; S A Levakov; I A Kulikov (IP Berlin A.V., 2014)
Surgical menopause is a pathology of women of reproductive age, developing after surgical removal of the ovaries to the uterus or without a uterus. Severe estrogen-deficient state has been progressing for 1-2 days after surgery, and therefore the hormone replacement therapy should be initiated in the first days and weeks after surgery. In women with postovariectomy syndrome and hysterectomy an unopposed estrogen monotherapy may be conducted. When expressed vegetative-vascular symptoms of menopause after surgery recommended the appointment of estriol (Ovestin) 2 mg orally 2-4 times per day (up to 8 mg) for 4 weeks. After reliever dose is gradually reduced to 1-2 mg/day. As a rule, women with hysterectomy may be administered estrogen alone without the addition of progestogen for 5 years or more.